A eficácia dos direitos fundamentais nas relações privadas: constitucionalizando o contrato na socialização do direito e a (in)suficiente análise da questão pelo Supremo Tribunal Federal - Leonel, Ana Leticia Anarelli Rosati (Universidade do Vale do Rio dos Sinos, 2014)
In the context of application of the Constitution to contractual relations, the dissertation discusses at first the structural transformation according to the changes of association, allocating it, especially in the context of a democratic state. The theses of legal individualism weakens, reaching the freedom of contract and, consequently, individual autonomy. The aim is thus to demonstrate that there is a clear overcoming the dichotomy between Public Law and Private Law at the current stage of the state, and seeks an effect of unity of the legal system. Thus, with the constitutionalization of contract and the radiating effect of the Constitution justifies the effectiveness of fundamental rights in private relations. At this point, too, if addresses to private autonomy as a fundamental right and the consequences of its collision with other principles. Analyzes the weighting fundamental principles, especially according to the technique of weighting. Finally, evaluate the effectiveness of fundamental rights in private relations in accordance with the normative vision of the Federal Constitution, approaching the indirect application, the direct application, criticism of both theories and presenting the consideration that may not exist uniform response to specific cases. After shows up the question of the applicability of the theory of fundamental rights in private relations in the Supreme Court, showing the current approach in the Brazilian Supreme Court.
Keywords: Contratos; Direitos fundamentais; Eficácia; Contracts; Fundamental rights; Efficacy; ACCNPQ::Ciências Sociais Aplicadas::Direito